PENGARUH BUDGET PLANNING MODEL TERHADAP KINERJA PENYUSUNAN ANGGARAN PEMERINTAH DAERAH KABUPATEN LAMPUNG TIMUR - Didik Prayitno; Einde Evana; Usep Syaipudin (Faculty of Economics and Business, 2019)
The purpose of this study was to determine the effect of budget participation, budget communication and budget details on the performance of local government budgeting. The object of this research is employees who work in the Government of East Lampung Regency and taken 3 people consisting of SKPD Leaders, Treasurers, and Planning (Kasubbag/Kasi). A total sample of 162 came from 54 SKPD and the analysis tool used was multiple linear regression. The results showed that budgetary participation, budget communication and budget detail had positive effect on the performance of the budget preparation of the East Lampung Regency Government. The more SKPD leaders carry out detailed budget oversight functions, they will be able to reduce the occurrence of budget irregularities, so that the performance of budget preparation is better. Suggestions proposed in this study are: The Government of East Lampung Regency has to improve capabilities and encourage more active participation by providing education programs and training on a regular budget preparation to the employees. SKPD Leaders involve more employees who are involved in budgeting activities during the implementation of the East Lampung Regency Development Plan Deliberation (Musrenbang) from the subdistrict level to the district level deliberation. East Lampung Regency Government has to use the budgeting system with the E-Budgetting System to avoid budget irregularities. Future studies are suggested including other variables outside the budget planning model variables as moderating variables to measure the performance of budgeting.